Performance of image watermarking algorithm using RSA with Fibonacci transform against attacks - Mahad, Zahari; Salim, Nur Raidah; Abdullah, Kamilah; Halim, Suhaila Abdul; Zulkafli, Nurul Aina Syafiqah (Taylor's University, 2023)
The protection of digital information has been the centre of attention as it can be transferred via the Internet, which may allow irresponsible parties to exploit the flaws in security. One such technique to protect digital information is digital image watermarking. This article introduces a watermarking algorithm using Discrete Wavelet Transform and Modified RSA Cryptosystem to secure the digital image. A secret image, which is to be protected, is embedded into a cover image. Several attacks are applied to the watermarked image to test the robustness of the embedded secret image. The metrics used to evaluate its performance are the peak signal-to-noise ratio and structural similarity index measure. Finally, it is compared with existing methods.